NICHD Study of Early Child Care and Youth Development: Phase II, 1996-1999 (United States) ([Verlag nicht ermittelbar], 2009)
The overall purpose of this study was to examine the influence of variations in early childcare histories on the psychological development of infants and toddlers from a variety of family backgrounds. This general objective was addressed through a prospective, longitudinal study of the experiences of 1,364 children and their families, which took into account the complex interactions among child characteristics and those of the human and physical environments in which the children were reared. Research Goals The specific research aims were as follows: Examining the relationship between infants' childcare arrangements (defined in terms of hours, type, quality, and stability of care and the age at which the child entered care) and children's concurrent and long-term development. Specifically, the study investigated the association between children's experiences in childcare and their social, emotional, language, and cognitive development. The social-emotional assessments included measures of attachment, independence, compliance, behavior problems, prosocial and antisocial behavior, and general competence in interacting with peers. Cognitive variables include general developmental level and problem solving skills. Language assessments incorporated measures of children's expressive and receptive communicative competence. Examining whether the social ecology of the home moderates the effects of childcare, i.e., whether children from different home environments are differentially affected by similar childcare experiences. The study examined the moderating effects of parents' values and attitudes, psychological adjustment and mental health, stress and social support, child-rearing practices, time use, interactions with the child, the marital relationship, and family demographics. Examining whether individual differences among children moderate the effects of infant care on child development. The study examined the moderating effects of such child characteristics as age, sex, health, birth order, and temperament. Identify demographic and family characteristics associated with families' childcare decisions. The study examined whether specific childcare arrangements are related to the parents' social class, marital status, psychological adjustment and personality, child-rearing values and attitudes, parenting practices, stress, social support, marital relationship, and the availability of childcare in the community. Provide a natural history of infant care in the 1990s, and help establish a baseline of data pertaining to the kinds of care being used by families. Whereas other national databases, such as those provided by the United States Census Bureau, provide static estimates of the number of children in different types of childcare, this network study supplements that knowledge with longitudinal data on successive enrollments into day care at various ages, patterns of arrangements used concurrently and over time, and the stability of arrangements during the first three years of life. One of the most valuable aspects of the collaborative study is the opportunity it provides to obtain a more complete and accurate picture of patterns of infant care used by families today. Census surveys use only gross categories of care (e.g., center vs. in-home). In this study, more fine-grained information regarding the types of centers and home-care facilities was gathered. Examine the consequences for families of maternal employment and childcare choices. Family relationships, parental mental health, family stress, and so on, are not just inputs to child development or moderators of childcare effects, they are also outcomes. High-quality childcare may alleviate family stress and enhance parental adjustment. Low-quality childcare may add to the stress parents experience. Although the main focus in the study was on the effect of childcare on the child, the study also examined the effect of childcare on the family. Identify demographic characteristics of childcare associated with childcare quality. Of interest to policy makers is another aspect of the study, the investigation of those regulatory characteristics that predict care of higher quality. These characteristics included the level and type of caregiver training, the size of the childcare group, the auspices of the childcare program (public/private, profit/nonprofit, independent/chain, employer-sponsored/church-based), whether the facility was licensed or unlicensed, the level of payment and fees, and whether the caregiver was a relative of the family. Data File Organization 193 data files were compiled for this study and are organized into three main groups: Analytical Data Sets (ADS) -- The raw data were examined and composites defined by small groups of individual principal investigators according to the demographic, family, childcare, and child outcome content of the data. The psychometric and distributional qualities of the variables along with site differences were examined. A set of variables that was psychometrically and distributionally acceptable to be used in analytic analyses was designed to test the study hypotheses. These data files comprise Parts 1-24 of the study data material. Supplemental Data Sets -- New and revised analysis variables as well as across-time mean scores and primary composites were produced as a supplement to the original Analytical Data Sets. These data files comprise Parts 25-27 of the study data material. Raw Data Sets -- The raw data were made available and comprise Parts 28-193 of the study data material. Training Workshop Recordings A three day summer training workshop on the SECCYD was put on by the NICHD at the Inter-University Consortium for Political and Social Research in Ann Arbor, Michigan. Recordings of that workshop, coordinated with the Powerpoint slides used during presentations, are freely available to the public at the addresses described below. Day One Part I (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1630) Introductions and Participant Research Questions - James Griffin Overview of Study - James Griffin Schedule of Data Collection - Bonnie Knoke Demographic Data - Bob Bradley Day One Part II (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1632) Family Data - Margaret Owen Orientation to using the Data and Documentation - Bonnie Knoke Day One Part III (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1633) Data Documentation: Hands-on Training - Bonnie Knoke Day One Part IV (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1634) Data Orientation: Merging Data Files - Robert Corwyn Child Care Data - Margaret Owen Day One Part V (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1635) Secondary Data Analysis - Peg Burchinal Day One Part VI (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1636) NICHD Funding Opportunities - James Griffin Day Two Part I (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1637) Social Data - Martha Cox Peer Data - Martha Cox Cognitive Data - Dan Keating Day Two Part II (http://lecb.physics.lsa.umich.edu/CWIS/browser.php?ResourceId=1638) School Data - Renate Houts Out-of-school Data - Bob Bradley Health Data - Bob Bradle...